2014
DOI: 10.4103/1119-3077.141423
|View full text |Cite
|
Sign up to set email alerts
|

Patients′ satisfaction with eye care services in a Nigerian teaching hospital

Abstract: Majority of the patients were satisfied with the services received. The major dissatisfaction points were cost of services and inadequate toilet facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 7 publications
9
27
5
Order By: Relevance
“…While studies that have expressly assessed patients' satisfaction with health information management personnel services seems scanty, some have done so in a rather comparative manner. For instance, studies have revealed patients are usually least satisfied with the health information management personnel services in comparison with services provided by doctors and nurses (Eke et al, 2014;Ezegwui et al, 2014;Ogunfowokan & Mora, 2012). Since this study did not set out to compare patients' satisfaction across various service points, it can be asserted that this study's findings do not correspond with the studies above.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…While studies that have expressly assessed patients' satisfaction with health information management personnel services seems scanty, some have done so in a rather comparative manner. For instance, studies have revealed patients are usually least satisfied with the health information management personnel services in comparison with services provided by doctors and nurses (Eke et al, 2014;Ezegwui et al, 2014;Ogunfowokan & Mora, 2012). Since this study did not set out to compare patients' satisfaction across various service points, it can be asserted that this study's findings do not correspond with the studies above.…”
Section: Discussioncontrasting
confidence: 56%
“…Specifically, the patient were more satisfied with the attitude of the doctors and nurses than with the medical records personnel (Ezegwui, Okoye, Aghaji, Okoye, & Oguego, 2014). Similarly, a study of children attending outpatient clinics of the University of Nigeria Teaching Hospital revealed that the majority of the respondents were satisfied with the overall quality of care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studying patient satisfaction regarding eye care services at tertiary hospital of central India. Ezegwui et al [5] noted that the cost of services was a major source of dissatisfaction while studying Patients' satisfaction with eye care services in a Nigerian teaching hospital in south-east Nigeria. This is at variance with the finding of Ademola-Popoola et al [6] where most of the patients perceived the cost of services to be affordable.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the eye care system should aim at adopting a patient oriented system to ensure maximum patient satisfaction [4]. Patients' perception of eye care services is a reflection of their satisfaction and has been noted to vary from that of the service providers [5]. Determinants of patients' overall satisfaction with received care have been noted to include the medical aspects of care such as trained personnel, use of appropriate medication and proper instruments, and the use of newer technologies [4]; as well as the non-medical aspect of care such as waiting time, assess to available services and communication [4].…”
Section: Introductionmentioning
confidence: 99%